Extreme weather‐year sequences have nonadditive effects on environmental nitrogen losses. (21st September 2017) - Iqbal, Javed; Necpalova, Magdalena; Archontoulis, Sotirios V.; Anex, Robert P.; Bourguignon, Marie; Herzmann, Daryl; Mitchell, David C.; Sawyer, John E.; Zhu, Qing; Castellano, Michael J.
Abstract: The frequency and intensity of extreme weather years, characterized by abnormal precipitation and temperature, are increasing. In isolation, these years have disproportionately large effects on environmental N losses. However, the sequence of extreme weather years (e.g., wet–dry vs. dry–wet) may affect cumulative N losses. We calibrated and validated the DAYCENT ecosystem process model with a comprehensive set of biogeophysical measurements from a corn–soybean rotation managed at three N fertilizer inputs with and without a winter cover crop in Iowa, USA. Our objectives were to determine: (i) how 2‐year sequences of extreme weather affect 2‐year cumulative N losses across the crop rotation, and (ii) if N fertilizer management and the inclusion of a winter cover crop between corn and soybean mitigate the effect of extreme weather on N losses. Using historical weather (1951–2013), we created nine 2‐year scenarios with all possible combinations of the driest ("dry"), wettest ("wet"), and average ("normal") weather years. We analyzed the effects of these scenarios following several consecutive years of relatively normal weather. Compared with the normal–normal 2‐year weather scenario, 2‐year extreme weather scenarios affected 2‐year cumulative NO3 − leaching (range: −93 to +290%) more than N2 O emissions (range: −49 to +18%). The 2‐year weather scenarios had nonadditive effects on N losses: compared with the normal–normal scenario, the dry–wet sequence decreased 2‐year cumulative N2 O emissions while the wet–dry sequence increased 2‐year cumulative N2 O emissions. Although dry weather decreased NO3 − leaching and N2 O emissions in isolation, 2‐year cumulative N losses from the wet–dry scenario were greater than the dry–wet scenario. Cover crops reduced the effects of extreme weather on NO3 − leaching but had a lesser effect on N2 O emissions. As the frequency of extreme weather is expected to increase, these data suggest that the sequence of interannual weather patterns can be used to develop short‐term mitigation strategies that manipulate N fertilizer and crop rotation to maximize crop N uptake while reducing environmental N losses. Abstract : The sequence of extreme weather years (i.e., dry vs. wet) affects 2‐year cumulative environmental nitrogen losses. The left panel displays annual average temperature and precipitation in central Iowa, USA from 1951 to 2012. The right panel displays 2‐year cumulative nitrous oxide emissions as they are affected by the sequence of weather years. In particular, the sequence of dry–wet vs. wet–dry years has different effects on N2 O emissions relative to "normal" weather years. Cover crops mitigate these extreme‐weather effects.